The Effect of Cherry Leaves Extract (Muntingia calabura) on Growth Performance of White Shrimp (Litopenaeus vannamei) - Shurathil Uyun; Ayu Adhita Damayanti; Fariq Azhar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Cherry leaf is a natural ingredient that can be used as a feed additive because it contains flavonoids, tannins, saponins, triterpene and polyphenols which are antioxidants. This study aims to determine the effect of giving cherry leaf extract on the growth of vaname shrimp. A total of 20 vannamei shrimp in the PL-20 phase measuring ÃÂ± 0.1g / head are kept in a 40 liter container. The method used in this study was an experimental method using a completely randomized design (CRD) with 4 treatments and 3 replications, namely P1: feeding without cherry leaf extract (control), P2: feeding with the addition of 1% cherry leaf extract, P3: feeding with the addition of 2% cherry leaf extract and P4: feeding with the addition of 3% cherry leaf extract. The data obtained were analyzed by ANNOVA test with a confidence level of 95% and Duncan's continued test. The results of this study indicate that the addition of cherry leaf extract can affect the growth of vaname shrimp, but has no effect on the FCR value and survival rate. The addition of cherry leaf extract to a concentration of 3% can increase the growth of absolute weight and length and the specific growth rate of vaname shrimp which is better than the treatment without the addition of cherry leaf extract. Therefore cherry leaf extract has the potential to be used as a feed additive.